CLINICAL MANAGEMENT AND REHABILITATION STRATEGY FOR WRESTLERS WITH PRE-EXISTING POST-TRAUMATIC GONARTHROSIS IN THE POST-ACUTE REHABILITATION PHASE AFTER RE-INJURY OR SURGICAL INTERVENTION - Tonkopei, Yuliia; Buhaienko, Tetiana; Lazorenko, Serhii; Shevchuk, Iuliia; Kozhemiako, Tetiana; Torhach, Sofiia (Eastern Ukrainian Medical Journal, 2026)
Introduction. Post-traumatic knee osteoarthritis in combat sports athletes is characterized by an aggressive clinical course due to constant axial and rotational overloads. Traditional rehabilitation approaches often neglect the specificity of the autonomic status and neuromuscular control in the post-acute period, leading to early disability. The study aimed to trace the dynamics of functional and structural changes in wrestlers with PTOA under the influence of the developed "Wrestle-Knee Rehab" clinical management strategy.Material and methods. A prospective study involved 32 wrestlers aged 22–35 with verified Stage I–II PTOA. The 8-week rehabilitation program was based on the International Classification of Functioning, Disability and Health (ICF) architecture and included four stages: immobilization, early and late post-immobilization, and pre-training. Assessment was performed using high-frequency ultrasonography, goniometry, the Lovett scale, and KOOS and WOMAC questionnaires. Statistical analysis was conducted using Wilcoxon and Spearman criteria (p<0.05).Results. The implementation of the strategy allowed for the elimination of active extension deficit (p < 0.01) and restoration of flexion range to 142.3°. Ultrasound monitoring showed regression of synovitis (reduction of effusion from 8.5 mm to<1.5 mm) and an increase in hyaline cartilage thickness from 1.8 mm to 2.2 mm. Muscle strength on the Lovett scale increased from 0.58 to 4.48. The most significant improvement on the KOOS scale was recorded in the “Sport and Recreation” subscale (from 22.4 to 79.8 points), indicating the restoration of the specific motor stereotype.Conclusions. It has been proven that the combination of structural damage and proprioceptive deficit necessitates active clinical management specifically during the post-acute period. The implementation of a four-stage rehabilitation program ensured the complete elimination of extension deficit and the attainment of physiological range of motion. A significant increase in muscle strength on the Lovett scale, alongside a decrease in the WOMAC index, confirmed the restoration of neuromuscular control. The most substantial improvement in KOOS scores within the «Sport and Recreation» domain verified the wrestlers’ readiness for a safe return to professional sports.